PROVISION OF THE PRINCIPLE OF COMPETITIVENESS IN THE CRIMINAL PROCESS OF UKRAINE - Рибікова, Ганна Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Objective: to investigate the specific problems that occur when securing the principle of competitiveness in the criminal process of Ukraine and to identify ways to solve them. Research methodology: in the work the dialectical method of cognition, general scientific and special methods was used. Findings: proposals were developed to interpret the grounds of competitiveness based on a dichotomy in prosecutor activity. Discussion: finding ways to improve the criminal procedural legislation in terms of ensuring a competitive basis. The principle of competitiveness and equality of the parties in the collection and presentation of evidence still includes elements of the declaration, since despite the advantages of protection laid down in the CPC concept of Ukraine, the prosecution party is in fact more empowered to form an evidence base. Accordingly, scientific reflection on the disproportion in the provision of evidence by the parties is needed. In Art. 129 of the Constitution of Ukraine stipulates that one of the main principles of the judiciary is the competitiveness of the parties, which is the freedom to give evidence and prove their conviction. Thus, Art. 22 of the CРС of Ukraine states that criminal proceedings are conducted on the basis of a competitive process, which involves the independent prosecution of the prosecution party and the party protecting their legal positions, rights, freedoms and legitimate interests by the means provided by this Code. The experience of social management points to the competitive relationships used for social regulation and social control to take into account their potential, in particular in the judiciary. In order to ensure proper conditions for the defense party at the stage of gathering evidential information, scientists have expressed the need to launch a parallel lawyer investigation in criminal proceedings as a separate institute of criminal procedural law, which consists in the independent implementation in the special procedural form of the system of practice of the system. Thus, in criminal procedural science, the search for the optimal model for ensuring the basis of competitiveness in criminal proceedings is continuing for our legal system. It is obvious that there is a need for the active protection of the collecting of evidentiary information by the defense party, which should be directed to the legislator in the direction of reducing the obstacles in obtaining the protector's evidentiary information. We believe that the idea of a parallel criminal investigation in criminal proceedings has some potential.